Pelatihan Daring Pembuatan Video Perjalanan Virtual Berbahasa Inggris bagi Pemandu Wisata Tersertifikasi dari Berbagai Daerah di Indonesia - Subekti, Adaninggar Septi; Wati, Mega; Susyetina, Arida; Kurniawati, Lemmuela Alvita; Ermerawati, Anesti Budi; Winardi, Andreas (Universitas Nusantara PGRI Kediri, 2023)
This community service activity was conducted in the form of online training, focusing on using English for designing virtual travel videos. Participants of this nation-wide training are 25 certified tour guides from various regions in Indonesia, out of 180 registrants. With Atourin as the training partner, the training aimed to facilitate the tour guide participants to be able to make virtual tour videos in English to promote tourism destinations to foreigners who would enjoy them from their homes during the Covid-19 pandemic. The training was conducted for two months in seven meetings via the Zoom platform with each meeting lasting for 120 minutes. At the end of the training, the participants were able to make virtual travel videos promoting tourism destinations in their respective areas. As seen from the participants’ enthusiasm for learning and their activeness in each meeting, it could be concluded that the training was a success. The training refreshed the tour guide participants’ English and improved their mastery before coming back to the tourism industry post-pandemic. Evaluation of the overall programme was conducted as an effort to improve the quality of a similar programme in the future, including conducting hybrid activities synchronously combining offline and online modes, allowing flexibility where participants can choose the mode with which they are more convenient.